Effects of hydrogen sulfide on the heme coordination structure and catalytic activity of the globin-coupled oxygen sensor AfGcHK - Fojtikova, Veronika; Bartosova, Martina; Man, Petr; Stranava, Martin; Shimizu, Toru; Martinkova, Marketa (Biometals, 2016)
AfGcHK is a globin-coupled histidine kinase that is one component of a two-component signal transduction system. The catalytic activity of this heme-based oxygen sensor is due to its C-terminal kinase domain and is strongly stimulated by the binding of O2 or CO to the heme Fe(II) complex in the N-terminal oxygen sensing domain. Hydrogen sulfide (H2S) is an important gaseous signaling molecule and can serve as a heme axial ligand, but its interactions with heme-based oxygen sensors have not been studied as extensively as those of O2, CO, and NO. To address this knowledge gap, we investigated the effects of H2S binding on the heme coordination structure and catalytic activity of wild-type AfGcHK and mutants in which residues at the putative O2-binding site (Tyr45) or the heme distal side (Leu68) were substituted. Adding Na2S to the initial OH-bound 6-coordinate Fe(III) low-spin complexes transformed them into SH-bound 6-coordinate Fe(III) low-spin complexes. The Leu68 mutants also formed a small proportion of verdoheme under these conditions. Conversely, when the heme-based oxygen sensor EcDOS was treated with Na2S, the initially formed Fe(III)-SH heme complex was quickly converted into Fe(II) and Fe(II)-O2 complexes. Interestingly, the autophosphorylation activity of the heme Fe(III)-SH complex was not significantly different from the maximal enzyme activity of AfGcHK (containing the heme Fe(III)-OH complex), whereas in the case of EcDOS the changes in coordination caused by Na2S treatment led to remarkable increases in catalytic activity.
Keywords: Phosphorylation; fosforylace; hem; Histidine kinase; Myxococcales; mutageneze cílená; histidinkinasa; molekulární struktura; biokatalýza; Molecular Structure; Hydrogen sulfide; Hydrogen Sulfide; Oxygen; kyslík; Kinetics; Intramolecular catalytic regulation; Histidine Kinase; Biocatalysis; sulfan; Heme-based oxygen sensor; Mutagenesis, Site-Directed; Autophosphorylation; Heme; Two-component signal transduction; kinetika